SPATIAL DISTRIBUTION OF TREE BIOMASS IN RUVU NORTH FOREST RESERVE TANZANIA - Sumarga, Elham (MAJALAH ILMIAH GLOBE, 2008)
Deforestation has been occurring rapidly in Ruvu North Forest Reserve (RNFR). The main cause of the deforestation is the tree biomass (wood) extraction for charcoal and fuelwood. The objectives of this study were to assess tree biomass, to measure the relationship between tree biomass and same remote sensing data, and to create tree biomass map of RNFR. Stratified sampling was applied as sampling method to get field data (tree DBH). Tree biomass was assessed by using allometric equation of Brown (1997). Furthermore, the relationship between tree biomass and some remote sensing data, such as vegetation indices and forest canopy density, was measured. Finally, tree biomass data were extrapolated based on the vegetation types to produce tree biomass map of RNFR. The estimated values of total tree biomass in RNFR range from 680,190.785 ton to 737,110.53 ton with average values ranging from 35.239 ton/ha to 38.188 ton/ha. Woodland has the highest tree biomass (26.34 ton/ha) while shrubland has the lowest one (8.71 ton/ha). Tree biomass in RNFR has a weak relationship with NDVI and TNDVI of SPOT image 2003, with correlation coefficient of -0.07 and -0.1. Tree biomass and forest canopy density of Landsat ETM image 2000 have a stronger relationship, with correlation coefficient of 0.58.ABSTRAKDeforestasi telah berlangsung secara cepat di Ruvu North Forest Reserve (RNFR). Penyebab utama deforestasi ini adalah pengambilan biomas pohon (penebangan) untuk pembuatan arang dan kayu bakar. Penelitian ini bertujuan untuk menghitung biomas pohon, mengetahui korelasi antara biomas pohon dan beberapa data remote sensing serta membuat peta biomas pohon di RNFR. Metode sampling yang digunakan untuk mengambil data lapangan (diameter pohon) adalah stratified sampling. Biomas pohon ditentukan dengan menggunakan persamaan allometric dari Brown (1997). Selanjutnya dihitung koefisien korelasi antara biomas pohon dan vegetation indices dari SPOT 2003 serta forest canopy density dari Landsat ETM 2000. Data biomas pohon selanjutnya diekstrapolasi berdasarkan tipe vegetasi untuk membuat peta biomass pohon di RNFR. Hasil penelitian menunjukkan bahwa nilai total biomas pohon di RNFR berkisar antara 680.190,785 ton sampai 737.110,53 ton dengan nilai rata-rata antara 35,239 ton/ha sampai 38,188 ton/ha. Woodland memilki biomas pohon tertinggi (26,34 ton/ha), sedangkan shrubland memiliki biomas pohon terendah (8,71 ton/ha). Biomas pohon memiliki korelasi yang lemah dengan NDVI dan TNDVI dari SPOT 2003 dengan koefisien korelasi -0,07 dan -0,1, namun memiliki korelasi yang lebih kuat dengan forest canopy density dari Landsat ETM 2000 dengan koefisien korelasi sebesar 0,58.Keywords: Tree Biomass, Biomass Map, Remote Sensing, Ruvu North Forest ReserveKata Kunci: Biomas Pohon, Peta Biomas, Penginderaan Jauh, Ruvu North Forest Reserve